FUZZY LOGIC METODE TSUKAMOTO UNTUK PREDIKSI PRODUKSI CPO DENGAN PERMINTAAN BERSIFAT STOKASTIK PADA PT. TOR GANDA - Naibaho, Frainskoy Rio (STMIK Budi Darma, 2019)
The best decision is the main goal in a problem. Decisions in the determination of stock Crude Palm Oil (CPO) the Palm Oil Mill Â is very important because it is directly in contact with the company's survival. Uncertain demand becomes a major problem in the sales of CPO, and so we need a system that can answer this question. Fuzzy logic is used in matters relating to the forecast with a high degree of accuracy. Fuzzy logic mapped the problem by first changing into linguistic mathematical conditions. Role created can answer many problems, including the problem of prediction. Fuzzy logic system consists of a subset of fuzzy and fuzzy rules. Fuzzy subsets represent different subsets of input and output variables. Fuzzy rules associated with input variables to the output variable via the subsets. Given the fuzzy rules which can be formed very flexible, then the fuzzy system can compute problems quickly and efficiently.Keywords: Fuzzy Logic, Tsukamoto, stochastic, inventories, CPO